A method for isolation of cone photoreceptors from adult zebrafish retinae. Issue 1 (December 2016) - Glaviano, Antonino; Smith, Andrew; Blanco, Alfonso; McLoughlin, Sarah; Cederlund, Maria; Heffernan, Theresa; Sapetto-Rebow, Beata; Alvarez, Yolanda; Yin, Jun; Kennedy, Breandán
Abstract Background Cone photoreceptors are specialised sensory retinal neurons responsible for photopic vision, colour perception and visual acuity. Retinal degenerative diseases are a heterogeneous group of eye diseases in which the most severe vision loss typically arises from cone photoreceptor dysfunction or degeneration. Establishing a method to purify cone photoreceptors from retinal tissue can accelerate the identification of key molecular determinants that underlie cone photoreceptor development, survival and function. The work herein describes a new method to purify enhanced green fluorescent protein (EGFP)-labelled cone photoreceptors from adult retina of Tg(3.2gnat2:EGFP ) zebrafish. Results Methods for dissecting adult zebrafish retinae, cell dissociation, cell sorting, RNA isolation and RNA quality control were optimised. The dissociation protocol, carried out with ~30 retinae from adult zebrafish, yielded approximately 6 × 106  cells. Flow cytometry cell sorting subsequently distinguished 1 × 106  EGFP+ cells and 4 × 106 EGFP− cells. Electropherograms confirmed downstream isolation of high-quality RNA with RNA integrity number (RIN) >7.6 and RNA concentration >5.7 ng/µl obtained from both populations. Reverse Transcriptase-PCR confirmed that the EGFP-positive cell populations express known genetic markers of cone photoreceptors that were not expressed in the EGFP-negative cell population whereas a rod opsin amplicon was only detected in the EGFP-negative retinal cell population. Conclusions This work describes a valuable adult zebrafish cone photoreceptor isolation methodology enabling future identification of cone photoreceptor-enriched genes, proteins and signalling networks responsible for their development, survival and function. In addition, this advancement facilitates the identification of novel candidate genes for inherited human blindness.